Rancang Bangun Robot 6WD Sebagai Alat Pemantau Kebocoran Gas Berbahaya Berbasis Komunikasi Wireless XBee-PRO Series1 60mW - Swamardika, IBA; Budiastra, I Nyoman; Setiawan, I Nyoman; Hendrayanto, Made Yogi (Majalah Ilmiah Teknologi Elektro; Vol 14 No 1 (2015): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i01p11)
The aim of this study is to help a company gas or chemical companies to determine the point of a gas leak. To find out the point of the gas leak, it is necessary to create a robot capable of exploring the underground passageway and has the ability to detect scent strength of gas, so that the point of the leak can be found .. One of the application of robotics technology in accordance with the conditions of underground passageways are a robot that has a combination of Wheeled Robot Arm Robot and 6WD. Due to the design of the robot can roam the surface conditions are not flat and has the ability to balance its body. The results achieved in this study is that the robot can detect the presence of butane gas use TGS2600 sensor. In addition, the transmission of information from the robot to use XBee interface software has been successfully carried out. So that the operator controls the robot can monitor the condition of the robot. Delivery of image information from the robot to the operator can be performed via the S-video channel then transferring images from the camera to the laptop.
Keywords: 6 WD, TGS2600, Xbee